First impressions of the functions and hafting technology of Still Bay pointed artefacts from Sibudu Cave - Lombard, M. (Southern African Humanities, 2021)
The exceptional preservation of organic material at Sibudu Cave has made residue analysis feasible on newly discovered Still Bay bifacial stone tools. A glimpse into the livelihoods and skills of people living at the site during the Still Bay is provided by use-traces that suggest hafting technology as well as butchery and hunting activities. Because the sample size is small, raw data are discussed for single tools. Although I am not prepared to make generalised interpretations for the Still Bay of South Africa from these results, they provide a solid base for formulating working hypotheses that can be tested with more extensive samples, both from Sibudu Cave and other sites. This study also proved useful for testing existing hypotheses based on typological and technological analyses of pointed Still Bay artefacts. To cite this article: Lombard, M. 2006. First impressions of the functions and hafting technology of Still Bay pointed artefacts from Sibudu Cave. Southern African Humanities 18(1): 27-41.